Pragmatics and non-verbal communication - Wharton, Tim. (Cambridge, UK ; New York : Cambridge University Press, 2009)
"The way we say the words we say helps us convey our intended meanings. Indeed, the tone of voice we use, the facial expressions and bodily gestures we adopt while we are talking, often add entirely new layers of meaning to those words. How the natural non-verbal properties of utterances interact with linguistic ones is a question that is often largely ignored. This book redresses the balance, providing a unique examination of non-verbal behaviours from a pragmatic perspective. It charts a point of contact between pragmatics, linguistics, philosophy, cognitive science, ethology and psychology, and provides the analytical basis to answer some important questions: How are non-verbal behaviours interpreted? What do they convey? How can they be best accommodated within a theory of utterance interpretation?"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Nonverbal communication; Body language